DESEMPENHO TÉRMICO DE EDIFICAÇÃO EM MÓDULO DE CONTÊINER MARÍTIMO - Viana, Françoíse; Souza, Henor Artur de; Gomes, Adriano (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Civil construction is currently facing challenges in building in a more economical and environmentally correct way. In this work, the objective is to know better the unconventional equipment used for buildings, the container, evaluating its thermal performance. Since in Brazil, its use in construction is recent, so an analysis is needed to understand how to adapt it efficiently. In this study, the thermal performance of the container is evaluated through numerical simulation using the Energyplus program, observing the construction of the building and considering the climatic conditions for the bioclimatic zone 3, foreseen in the NBR 15220 standard, also observing the minimum requirements of the norm NBR 15575. For the study is projected a house with 2 modules of container totaling an area of 29.57m². The results show the need for adaptations for the container to have habitability in the analyzed bioclimatic zone. The use of thermal insulation in the closures, a cover, a foundation and lighter colors in the external closure provide a better thermal performance of the building.